Animal Models for Investigating the Central Control of the Mammalian Diving Response - Mcculloch, Paul (Frontiers in Physiology, 2012)
Pioneering studies by Per Scholander indicated that the diving response consists of reflexly induced apnea, bradycardia and an alteration of blood flow that maintains perfusion of the heart and brain. More recently field physiological studies have shown that many marine animals can adjust cardiorespiratory aspects of their diving response depending upon the behavioral situation. This could suggest that the very labile heart rate during diving is under direct cortical control. However, the final control of ANS functioning resides within the brainstem and not the cortex. Many physiologists regard the brain as a “black box” where important neuronal functioning occurs, but the complexity of such functioning leaves systematic investigation a daunting task. As a consequence the central control of the diving response has been under-investigated. Thus, to further advance the field of diving physiology by understanding its central neuronal control, it would be first necessary to understand the reflex circuitry that exists within the brainstem of diving animals. To do this will require an appropriate animal model. In this review, two animals, the muskrat and rat, will be offered as animal models to investigate the central aspects of the diving response. Firstly, although these rodents are not marine animals, natural histories indicate that both animals can and do exploit aquatic environments. Secondly, physiological recordings during natural and simulated diving indicate that both animals possess the same basic physiological responses to underwater submersion that occur in marine animals. Thirdly, the size and ease of housing of both animals makes them attractive laboratory research animals. Finally, the enormous amount of scientific literature regarding rodent brainstem autonomic control mechanisms, and the availability of brain atlases, makes these animals ideal choices to study the central control of the mammalian diving response.